Revisiting the colour–magnitude relation of early-type galaxies in the Virgo cluster - González, Nélida Mabel (2011)
In this contribution, we revisit the colour–magnitude relation of the Virgo cluster by performing our own photometry and analysis on the images of 100 early-type galaxies observed as part of the Virgo Cluster Survey of the Advanced Camera for Surveys of the Hubble Space Telescope. We aim at disentangling whether the alleged non-linearity of the relation may be associated with an improper morphological classification of some galaxies of the sample.